Immunoglobulin Light Chain Amyloidosis (AL) Presenting as Periorbital Purpura in A 39 Years Female Patient (Journal of Medicine, 2015)
Immunoglobulin light chain amyloidosis (AL) is the most frequent form of amylodosis in adults, being more common in the elderly and male patients. The cutaneous manifestations occur in about 30% and are important clue do diagnosis. We report a 39 year-old-female patient with periorbital purpura, peripheral polyneuropathy and cardiomyopathy diagnosed as amyloidosis and treated with melphalan and prednisolone.J MEDICINE July 2015; 16 (2) : 122-123